Minimum wages and social policy - "Cunningham, Wendy V." (Washington D.C., 2007)
Unlike in the OECD, the minimum wage in Latin America and the Caribbean can be used to affect poverty and income inequality. However, the authors caution that policymakers must take care in setting the minimum wage level in conjunction with other social programs, such as unemployment safety nets, so as not to cause an increase in poverty.
Keywords: Minimum wages-Latin America